Spatial Analysis on Vulnerability to Dengue Hemorrhagic Fever in Kotabaru Subdistrict, Jambi Municipality, Jambi Province - Suhermanto -; Tri Baskoro Tunggul Satoto; Barandi Sapto Widartono (Tropical Medicine Journal, 2012)
Introduction: High incidence of DHF in Kotabaru Subdistrict was high even endemic in all villages. Utilization of Geographical Information System technology integrated with the wide of settlement land, the density of Aedes sp, maya index, resistance and transovarial of virDen, got a picture or map vulnerable areas prone event of DHF in Kotabaru Subdistrict.Objectives: This study to map areas vulnerable to dengue hemorrhagic fever is based on the highest incidence of DHF in Kotabaru Subdistrict, Jambi Municipality.Methods: This study is an observational survey with cross sectional design. The variable of the study was population density, the wide of settlement land, the density of Aedes sp. population, rainfall, vector vulnerability, and transovarial of virDen.Results: The result showed population density had no correlation to Dengue Hemorrhagic Fever (DHF) incidence, whereas the wide of settlement land (p=0.004) and population density of Aedes sp. (p=0.001) influenced DHF incidence. The number water containers controllable sites (89%) and percentage of Maya Index (p=<0.001) was high influenced DHF incidence. Rainfall not influenced DHF incidence. The vector resistance not influenced the high of DHF incidence and the high of DHF incidence was not influenced by transovarial of virDen. The high vulnerability to DHF in Kotabaru Subdistrict occurred in 2 villages and the intermediate vulnerability happens in 4 villages. The area with intermediate vulnerability generally have direct border to the village with high vulnerability category.Keywords: Spatial, Maya Index, Resistance, DHF